THE INFLUENCE OF GREEN ACCOUNTING AND PROFITABILITY ON THE FIRM VALUE OF THE COAL INDUSTRY IN 2019-2023 - Rahayu, Dewi Sri; Wicaksono, Achmad; Muzakki, Kafidin; Fahriani, Dian (JEA17: Jurnal Ekonomi Akuntansi, 2025)
The study aims to analyze the impact of green accounting implementation and profitability levels on the firm value of coal industry companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. Green accounting reflects a company's transparency in disclosing environmental-related costs, while profitability provides insights into its ability to generate profits. This research adopts a quantitative approach using descriptive methods and multiple linear regression analysis to evaluate the relationships between variables. The sample consists of 15 companies selected based on specific criteria. The findings indicate that the implementation of green accounting significantly affects firm value, as companies with more transparent environmental reporting tend to have higher valuations. Furthermore, profitability plays a crucial role in enhancing firm value, suggesting that companies with stable earnings are more attractive to investors. Overall, these two factors simultaneously influence firm value, although other variables also contribute. These findings highlight the importance of implementing green accounting as part of a sustainability strategy and improving profitability to strengthen a company's competitiveness in the capital market.